ACADEMICIAN LVOV’S DOCTRINE VS. NEO-LIBERAL DOCTRINE: COMPARISON OF THE REASEARCH PROGRAMS’ STRUCTURE AND LOGIC - B. Yerznkyan (Вестник университета, 2016)
The structural and logical features of the doctrine of Academician Lvov in comparison to the neo-liberal doctrine, formed the basis of market reforms in Russia, are considered. The reasons of insolvency of the latter and its unsatisfied consequences as well as the possibility of implementing the Lvov’s doctrine are discussed.